Role of parental socioeconomic status on their children’s education at District Mardan of Khyber Pakhtunkhwa, Pakistan - Ali, Abid; Jan, Azizullah; Ullah Khan, Ihsan; Zeb, Alam; Ahmad, Mansoor (Penerbit Universiti Kebangsaan Malaysia, 2021)
Education has been unequally disseminated to the deprived class due to socioeconomic that hardly receiving their rational piece. This research study aimed to find out the connection between socioeconomic factors and the academic performance of students in selected higher secondary schools in District Mardan, Khyber Pakhtunkhwa. A sample of 150 students was selected from three schools through the purposive sampling method. Data was collected through a structured questionnaire with five points Likert scale. The descriptive statistic, frequency, percentage and mean was used for basic information while inferential statistics were used for the correlation of the selected variables. The findings show that family size has a negative significant relationship, while parental education, income level and parental assistance have significant and positively related to the child’s education. While parental occupation and parental decision have non significant relationship with children educational outcomes. The study outcomes show that there is a significant and positive correlation between the socio-economic status of the parents with children’s academic performance. Consequently, it is suggested that the government has to make available schools that will accommodate and also provide an encouraging environment for all the students regardless of their family socioeconomic status.